2020
DOI: 10.21203/rs.3.rs-17486/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of gastrointestinal parasitism at recreational canine sites in the USA: the DOGPARCS study

Abstract: Background: The rapid growth in off-leash dog parks provides opportunity for canine socialization activities but carries risk of exposure to intestinal parasites. This study assessed the prevalence of these infections in dogs visiting off-leash dog parks.Methods: Fresh defecations were collected from dogs visiting parks in 30 metropolitan areas across the USA. Samples were analyzed by coproantigen immunoassay (CAI) (Fecal Dx® and Giardia Test, IDEXX Laboratories, Inc.) and zinc sulfate centrifugal flotation (C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 21 publications
3
9
0
Order By: Relevance
“…in 5.8% of samples. This is comparable (4%) with a large national survey in the US (Little et al) but lower than that reported in other studies using similar techniques reported by Stafford et al and Sweet et al [2,3,8]. Reliance on flotation alone, Giardia spp.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…in 5.8% of samples. This is comparable (4%) with a large national survey in the US (Little et al) but lower than that reported in other studies using similar techniques reported by Stafford et al and Sweet et al [2,3,8]. Reliance on flotation alone, Giardia spp.…”
Section: Discussionsupporting
confidence: 63%
“…Nematodes (hookworms, whipworms, and ascarids) collectively were present in 2.3% of dogs. Stafford et al reported values from 2.8% (west) to 17.1% (southeast) depending on the region of the USA where the samples were collected [8]. In a national study conducted in Canada, Villeneuve et al found higher prevalence of ascarids (8.2%) in Alberta and hookworm (5.6% nationally); however, dogs were surveyed from shelters, and the prevalence is likely higher than in client-owned dogs [9].…”
Section: Discussionmentioning
confidence: 99%
“…Dogs less than 1 year of age are at increased risk of nematode and Giardia spp. infections, and as the dog had no reported deworming since being adopted from the breeder, it is possible that the dog had intestinal parasitism leading to diarrhoea 7 . In the presence of increased losses through diarrhoea, a dog with hypodipsia may not be able to maintain hydration, resulting in hypernatraemia.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a number of both IP-and CP-treated dogs had Day 0 pre-treatment FEC numbers that were very high for the species identified (e.g. T. canis range of 1-1275 and 1-574 for IP and CP, respectively), in line with overdispersion of parasites in dog populations, but at the same time confirming the potentially high risk of environmental contamination by non-treated, infected dogs in home environments and those locations shared with other dogs [34,35]. The zoonotic potential of T. canis and pathogenic disease caused by A. caninum are well documented, including Europe [5-8, 32, 33].…”
Section: Discussionmentioning
confidence: 66%